Quantitative systematic review: Methods used for the in vivo measurement of body composition in pregnancy. - Guzman‐Ortiz, Elizabeth; Bueno‐Hernandez, Nallely; Melendez‐Mier, Guillermo; Roldan‐Valadez, Ernesto (Journal of Advanced Nursing (John Wiley & Sons, Inc.), 2021)
Aims: Because of the increased overall prevalence of pre‐pregnancy obesity among racial‐ethnic groups, we conducted a review of published methods for body composition measurement during pregnancy considering at present there is no consensus on the best practices and type of study design that researchers should use for this purpose. Design: Quantitative systematic review. Data Sources: PubMed, EMBASE, Scopus, Web of Science, and Virtual Library of Health. Search dates from 1997–2016. Review Methods: Search of articles indexed in selected databases from 1997–2016. Studies were published in English, Spanish, and Portuguese. Graphs were carried out using data visualization software. Results: From the 112 included studies, 70 were prospective cohorts, 30 cross‐sectional studies, 10 randomized controlled trial, and two retrospective studies. Cross‐sectional studies and randomized controlled trial depicted a positive correlation with significant trend. Conclusions: Although several methods for body composition measurement exist, only bioelectrical impedance analysis, displacement plethysmography, and displacement plethysmography show a significant growing trend. Use of data visualization allows understanding various associations among categorical variables, with a graphical display of their multidimensional behaviour. Impact: Public and private health‐care institution evaluating pregnancy women. Health‐care personnel, including nursing professional, dealing with measurements of body composition during pregnancy will find reading this manuscript beneficial.